Misi: Melindungi Negara. Agenda Rahasia: Tindak Asusila Sesama Jenis TNI di Balik Seragam ( Suatu penelitian di wilayah Pengadilan Militer III-12 Surabaya) - Beatrix Delania Pota (CV. KAMPUS AKADEMIK PUBLISING, 2025)
Sexual misconduct is a crime that can occur anywhere and affect anyone, including military personnel who have the duty and responsibility to protect the nation. Often, behind the uniform, there are actions that lead to the abuse of power by these individuals, undermining the integrity of institutions that are supposed to safeguard society. Through a qualitative approach, this research utilizes court decision data to explore the role of the legal system in revealing cases of moral and legal violations within the military environment. This study highlights the importance of transparency, accountability, and institutional reform to prevent similar actions in the future and ensure that the mission of national protection is not compromised by deviant behavior from individuals in uniform.